Kecakapan Lulusan Program Studi Teologi yang Menjawab Kebutuhan Gereja - Gidion Gidion (SANCTUM DOMINE: JURNAL TEOLOGI, 2021)
There are indications of dissatisfaction of graduate users of Kristus Alfa Omega Theological College's graduates' skill. Regarding this issue, the research focuses on: First, how big is the need of Pentecostal-Charismatic Churches on the provided qualification by Theology department in Kristus Alfa Omega Theological College? Second, how big is the need of the Pentecostal-Charismatic Churches in ministry-support media skill? Third, what is the holistic skill of Kristus Alfa Omega Theological College graduates needed most by the Pentecostal-Charismatic Churches? This research uses a quantitative research method with a descriptive study. The result was that 99.2% of the skill needed by Pentecostal-Charismatic Churches had been provided by the Theology Department of Kristus Alfa Omega Theological College. The five most graduate skill's needed are Bible interpreting skills, preaching, evangelizing, leadership, new ministry planting, character, spirituality, and multimedia. It is hoped that this research will become a consideration for any Theological Colleges in formulating its curriculum.